PEMBUATAN PETA REPOSISI BIDANG TANAH ANOMALI UNTUK MENINGKATKAN KUALITAS BIDANG TANAH DI PERUMAHAN MEGA REGENCY, DESA SUKARAGAM, KECAMATAN SERANG BARU, KABUPATEN BEKASI, JAWA BARAT - Diva Ardianto; Moch Angga Nursyeha; Muhamad Iqbal Firdaus; Putri Fifa Maulina; Riza Firdaus; Tiara Syifa Fauziah; Asri Ria Affriani; Ahmad Nur Fajar; Sajadi Sajadi; Muhammad Agus Purnama (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2023)
This study aims to improve the land parcel quality to improve the Mega Regency Housing Block K's spatial layout in Sukaragam Village, Serang Baru District, Bekasi Regency. The method used in this study is qualitative, with data collection techniques in the form of observation and documentation. The stages of the research carried out were (1) Primary and secondary data collection, (2) Data analysis, and (3) the final stage, which included map processing and plane repositioning using AutoCAD. The results of this study stated that the Mega Regency Housing Block K was by the GeoKKP Application, which resulted in the repositioning of 113 plots of land, village administration boundaries, 267 building use rights (HGB), 78 property rights (HM), 21 plots having multiple NIBs, 2 Public Facilities, and 12 Housing Blocks